Wilmot-Smith on construction contracts - Wilmot-Smith, Richard; Darling, Paul (Oxford : Oxford University Press, 2021)
This fourth edition continues to take a clear and practical approach to the law and practice relating to construction contracts in the UK. It provides comprehensive coverage of the substantive law and modern dispute resolution procedures in the field of construction and gives clear guidance when seeking difficult answers.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 16, 2021).
Keywords: Construction contracts -- England; Construction contracts -- Wales